Estudo da atividade biológica do motivo ECD do domínio tipo-desintegrina da botropasina - Ike, Priscila Tomie Leme (Universidade Federal de São Carlos, 2011)
Integrins are cell surface receptors that mediate cell adhesion and platelet aggregation, although they do part of important physiological processes in the organism, are also related pathologies such as tumorigenesis, metastasis and thrombosis. Thus integrins are important targets in development of drugs for the treatment of these diseases. Snake venoms metalloproteases (SVMPs) of PII and PIII class possessing a disintegrin domain, capable of binding to integrins inhibiting its activity, have been widely studied for this purpose. PII-SVMPs bind integrins via the RGD motif found in disintegrin domain. PIII-SVMPs have three domains: metalloprotease (M), disintegrin-like (D) with the ECD motif instead of RGD and 'Cysteine-rich' domain (C). PIII-SVMPs containing only DC domains are able to interact with integrins inhibiting cell adhesion and platelet aggregation. However it is not known which region of these molecules is involved in binding to integrins, and two regions are identified as likely responsible for integrin-ligand interactions: the motif ECD and a region called the hyper variable region (HVR) present in some PIII-SVMPs. The intention here was to assist the understanding of this interaction, assessing the importance of ECD motif present in disintegrin-like domain of Bothropasin, a PIIISVMP. For the three-dimensional structure of bothropasin, we have that in the ECD motif, aspartic residue (D) made a interaction with calcium ions, and cysteine (C) is involved in a disulfide bridge, but the glutamic acid (E) which is very reactive, is free to interact with other molecules. Thus, the proposal was to obtain a recombinant molecule consisting in the D and C domains of bothropasin (BDC) and a mutant molecule (BDC-ACD), where the glutamic residue of EDC motif present in disintegrin-like domain of BDC is replaced by a alanine residue. BDC-ACD, was obtained by PCR (Polymerase Chain Reaction) using the QuikChange@ Site-Directed Mutagenesis Kit, with the DNA template pGEX-4T-BDC and primers containing the desired mutation. The recombinant proteins were expressed in the soluble form in fusion with glutathione Stransferase protein. Purification of recombinants proteins was made in Glutathione Sepharose resin and the fusion proteins, immobilized on the resin were cleaved with enzyme thrombin. BDC and BDC-DCA were evaluated for their ability to inhibition of platelet aggregation which found that the mutation did not cause a significant change in protein activity, indicating that the glutamic residue of ECD motif is not involved in connection with integrins. Were also assayed for inhibition of adhesion of breast adenocarcinoma cells (MDA-MB- 231) to collagen and no inhibition was observed suggesting that, like the other PIII-SVMPs, BDC interact with α2 subunits of intergrins, which are not expressed in tested cells.
Biological activity study of ecd motif of disintegrinlike domain of bothropasin
Keywords: Química orgânica; Bioquímica; Desintegrinas; Serpentes; Metaloproteases; CIENCIAS EXATAS E DA TERRA::QUIMICA